Can environmental supervision improve air quality? Quasi-experimental evidence from China - Zou, Xuan; He, Yao; Zhang, Jincheng (Frontiers in Environmental Science, 2023)
Environmental supervision is significantly disrupted by local economic development and typically characterized by a lack of independence in China. This paper investigates the impacts and mechanisms of vertical management reform of the environmental department (EVM) in China on urban air quality. We construct a principal-agent model suitable for explaining the interactions between the central and local government and elaborate the intrinsic mechanism of EVM on strengthening the environmental supervision. Using manually collected data, we conduct the EVM as a quasi-experiment and construct a time-varying DID model. Our empirical results show that the environmental vertical reform significantly strengthens regional environmental supervision and reduces urban air pollution, bring abatement in PM2.5 concentration. The mechanism shows that the EVM increases enterprises' green innovation and attracts the new entrants, further promoting the industrial upgrading. Our study provides a new perspective on environmental governance and urban air quality in emerging countries such as China.